Nucleophilic substitution by amide nitrogen in the aromatic rings of [zn − H]˙+ ions; the structures of the [b2 − H − 17]˙+ and [c1 − 17]+ ions. Issue 16 (6th April 2016) - Mu, Xiaoyan; Lau, Justin Kai-Chi; Lai, Cheuk-Kuen; Siu, K. W. Michael; Hopkinson, Alan C.; Chu, Ivan K.
Abstract : Residue-specific [c1 − 17] + and [b2 − H − 17]˙ + fragment ions reveal a novel cyclic rearrangement between peptide backbones and sidechains. Abstract : Peptide radical cations that contain an aromatic amino acid residue cleave to give [z n − H]˙ + ions with [b2 − H − 17]˙ + and [c1 − 17] + ions, the dominant products in the dissociation of [z n − H]˙ +, also present in lower abundance in the CID spectra. Isotopic labeling in the aromatic ring of [Yπ ˙GG] + establishes that in the formation of [b2 − H − 17]˙ + ions a hydrogen from the δ-position of the Y residue is lost, indicating that nucleophilic substitution on the aromatic ring has occurred. A preliminary DFT investigation of nine plausible structures for the [c1 − 17] + ion derived from [Yπ ˙GG] + shows that two structures resulting from attack on the aromatic ring by oxygen and nitrogen atoms from the peptide backbone have significantly better energies than other isomers. A detailed study of [Yπ ˙GG] + using two density functionals, B3LYP and M06-2X, with a 6-31++G(d, p) basis set gives a higher barrier for attack on the aromatic ring of the [z n − H]˙ + ion by nitrogen than by the carbonyl oxygen. However, subsequent rearrangements involving proton transfers are much higher in energy for the oxygen-substituted isomer leading to the conclusion that the [c1 − 17] + ions are the products of nucleophilic attack by nitrogen, protonated 2, 7-dihydroxyquinoline ions. The [b2 − H − 17]˙ + ions are formed by loss of glycine from the same intermediates involved in the formation of the [c1 − 17] + ions.